2004
DOI: 10.1128/aem.70.2.937-942.2004
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable l -Lysine 6-Dehydrogenase from the Thermophile Geobacillus stearothermophilus Isolated from a Japanese Hot Spring: Characterization, Gene Cloning and Sequencing, and Expression

Abstract: L-Lysine dehydrogenase, which catalyzes the oxidative deamination of L-lysine in the presence of NAD, was found in the thermophilic bacterium Geobacillus stearothermophilus UTB 1103 and then purified about 3,040-fold from a crude extract of the organism by using four successive column chromatography steps. This is the first report showing the presence of a thermophilic NAD-dependent lysine dehydrogenase. The product of the enzyme catalytic activity was determined to be ⌬ 1 -piperideine-6-carboxylate, indicatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…In the case of saccharopine reductase, the substrates are glutamate and L-2-aminoadipate-6-semialdehyde, which form a Schiff base intermediate that is reduced by NADPH to saccharopine (76). Lysine 6-dehydrogenase catalyzes the oxidative deamination of the ⑀-amino group of lysine in the presence of NAD ϩ to form L-2-aminoadipate-6-semialdehyde (77).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of saccharopine reductase, the substrates are glutamate and L-2-aminoadipate-6-semialdehyde, which form a Schiff base intermediate that is reduced by NADPH to saccharopine (76). Lysine 6-dehydrogenase catalyzes the oxidative deamination of the ⑀-amino group of lysine in the presence of NAD ϩ to form L-2-aminoadipate-6-semialdehyde (77).…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that the enzyme was a dimer, similar to the A. tumefaciens enzyme (78 kDa) (7). This was in contrast to the hexameric enzyme (260 kDa) isolated from G. stearothermophilus (14). However, the A. denitrificans enzyme eluted as hexamer (240 kDa) when a high concentration of L-lysine (10 mM) was supplemented to both the enzyme solution and the elution buffer.…”
Section: Molecular Mass Subunit Structure and Amino Acid Sequencesmentioning
confidence: 47%
“…Our observations suggest that the dimeric enzyme itself exhibits catalytic activity and it assembled into a hexamer in the presence of L-lysine. Previous studies indicated that the A. tumefaciens enzyme associated as a tetramer (160 kDa) in the presence of L-lysine (7) and the G. stearothermophilus enzyme was a hexamer in the absence of L-lysine (14). Thus, the A. denitrificans enzyme is different from the A. tumefaciens enzyme and the G. stearothermophilus enzyme.…”
Section: Molecular Mass Subunit Structure and Amino Acid Sequencesmentioning
confidence: 88%
See 2 more Smart Citations